PENGARUH EFEKTIVITAS PELAKSANAAN PROGRAM REMEDIAL TERHADAP HASIL BELAJAR SISWA KELAS XI AKUNTANSI DI SMK LABOR BINAAN FKIP UNRI PEKANBARU - Hasna, Dia Rahmatul; Kartikowati, Sri; Haryana, Gani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The aim of this research is to figure out the effect of remedial program effectiveness on the students achivement. The population of this research is 25 students involved at remedial program at class XI Accounting in SMK Labor Binaan FKIP UNRI Pekanbaru. Data was collected by questiones and documentation techniques. The conclusion of the study showed that the implementation of remedial program at the SMK Labor Binaan FKIP UNRI Pekanbaru is generally in the effective category. While the students learning outcomes after the remedial program implemented get a value above the minimum completeness criteris in learning. Effective remedial program implementation and effect on the learning outcomes of class XI Accounting in SMK Labor Binaan FKIP UNRI Pekanbaru.Key Words: Effectiveness, Remedial Program, Student Learning Outcomes